PROCESSES OF FORMATION OF SODIUM BICARBONATE GROUNDWATER IN THE RAINWATER – SANDSTONE SYSTEM - S. Kh. Pavlov (Геодинамика и тектонофизика)
In modeling, a study was made of the processes of the physical-chemical interaction between rainwater and sandstone. It was stated that as a result of the interaction, already in mineralization of water equal to 55 mg/l, there emerges a pure soda solution whose sharp oxidation properties, retaining up to 200 mg/l, change to sharp restorative when exceeding this value. At the mineralization of water equal to 30 mg/l, an intensive increase in the number of hydroxide ions in a solution makes it highly alkaline. The active removal of calcium from solution is due to the formation of not only solid phase calcite, whose share does not exceed 15 %, but largely limonite, whose content is as high as 25 %. The accumulation of high concentrations of sodium in a solution is caused by the absence of its secondary mineral formations in a wide range of the rock/water ratios. Under reservoir conditions, the solution is composed of carbonate. This solution, transferred from reservoir to surface conditions, undergoes transformation in the result of interaction with the atmosphere. A decrease in pH of the solution resulted in the acquisition of sharp oxidation properties, with the cation, sulfate, fluorine and chlorine contents remained at the level corresponding to the reservoir conditions and the cardinal changes affected the carbonate system components and silicon compounds. Hydrosilicate ion was transformed into precipitated silicon oxide. Carbonate ions were transformed into hydrocarbonate, and the additional hydrocarbonate ions were formed for the solution to preserve a state of equilibrium after the removal of the representative number of hydrosilicate ions therefrom. An amount of carbon required for their formation was extracted from the atmosphere. The solution became hydrocarbonate, with hydrosilicate ions almost disappeared therefrom. Different calculation options for model solution, which is in equilibrium with the atmosphere, correlate with the representative group of soda-type groundwater. The calculation results are confirmed by field observations over the authigenic mineral formation on a large part of the Russian territory.